Think global, act local! A mechanism for global commons and mobile firms - Lassi Ahlvik; Matti Liski (Center for Economic Studies and ifo Institute (CESifo), 2019)
It is tricky to design local regulations on global externalities, especially so if firms are mobile. We show that when costs and outside options are firms' private information, the threat of firm relocation leads to local regulations that are stricter, not looser. This result is general and follows because policy-driven information rents act as targeted compensations to firms that can efficiently limit the externality. The optimal mechanism supplements this strict local regulation with a looser opt-in scheme, creating a global cap for externalities for a subset of firms. We illustrate the magnitude of these effects by providing a quantification of the optimal mechanism for the key sectors in the EU emissions trading system.
Keywords: D82; L51; Q54; Q58; 330; externalities; mechanism design; private information; climate change; emissions trading; carbon leakage